2014
DOI: 10.1111/eulj.12094
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Rights and Citizenship of the Union at a Crossroads: A Promising Alliance or a Dangerous Liaison?

Abstract: The reinforcement of the protection of fundamental rights at the European level and the emergence of the status of Union citizenship are two closely connected phenomena. European citizenship has been and continues to be one of the central arguments in favour of the extension of the scope of EU fundamental rights. This argument arises out of a sentiment that vindicates equality at the core of the citizenship of the Union as a fundamental status. Against this background, this paper examines the different possibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…65 A further step in the same direction would be to state that Union citizenship triggers the application of the Charter. 66 This approach, however, differs greatly from the traditional approach, which considers the scope of the Charter as a delimited ratione materiae. 67 The right to an effective remedy enshrined in Article 47 CFR has a long tradition in EU law and is accepted as general principle of EU law 'which underlies the constitutional traditions common to the Member States'.…”
Section: For a Reinterpretation Of Article 51(1) Cfrmentioning
confidence: 99%
“…65 A further step in the same direction would be to state that Union citizenship triggers the application of the Charter. 66 This approach, however, differs greatly from the traditional approach, which considers the scope of the Charter as a delimited ratione materiae. 67 The right to an effective remedy enshrined in Article 47 CFR has a long tradition in EU law and is accepted as general principle of EU law 'which underlies the constitutional traditions common to the Member States'.…”
Section: For a Reinterpretation Of Article 51(1) Cfrmentioning
confidence: 99%
“…65 Chavez-Vilchez seems to shed new light on a formula that was already defined as 'both uncertain and promising, for it provides for a new dimension in the legal design of the citizenship of the Union without specifying its core implications and material content'. 66 While the Court treads very carefully, it seems to suggest that in purely internal situations, the genuine enjoyment of the substance of citizenship rights could be impaired by an interference with family life in the Member State of nationality. This, in fact, comes close to the scenario that was alluded to as unlikely and tricky by Iglesias Sanchez in 2014, that is, 'admitting that any violation of fundamental rights would trigger the protection of the new formula, paving the way for a complete incorporation of EU fundamental rights against Member States'.…”
Section: Broadening the Concept Of Dependency And Shedding A New Ligh...mentioning
confidence: 99%
“…the intersection between European citizenship and fundamental rights is extremely complex to articulate without pushing the contours of one of them beyond the carefully builtup constitutional balances, since their underlying rationales give rise to significant tensions and difficulties when assessing the possible ways forward. 106 Most recently, Snell has suggested that extending the application of the Ruiz Zambrano doctrine presents constitutional challenges, and the Court seems to be 'relying on a circular argument where rights applying within the scope of the Treaty serve to determine that scope'. 107 We also recognize that 'undermining these limits is risky, even when it is done in the name of fundamental rights'.…”
Section: -202 (2020)mentioning
confidence: 99%